AN ANALYSIS OF THE SUSTAINABILITY OF THE CORAL REEF ECOSYSTEM IN THE MARINE PROTECTED AREAS OF WAETUNO AND KABITA VILLAGES, WAKATOBI REGENCY - Shaadikin, Rahman; Ridwan Hasan; Malik Ridwan (Jurnal Multidisipliner Bharasumba, 2025)
This study aims to determine the sustainability status of coral reef ecosystems based on five dimensions: ecology, economy, society, technology, and institutions. The research location is in Waetuno Village and Kabita Village, Wakatobi Regency, from March to August 2023. Data collection was conducted using survey methods and analyzed using the Rapid Appraisal Index of Coral Reef Management Sustainability (Rap-Insus-COREMAG) approach. The analysis results indicate that, out of the five dimensions examined, only the ecological dimension falls into the “good” category. Meanwhile, the economic, social, technological, and institutional dimensions are categorized as ‘adequate’ to “poor.” These findings indicate that while the ecological condition of the coral reefs is relatively well-preserved, other aspects supporting sustainable management still need to be significantly improved to achieve sustainable balance.